Estudo de propriedades ópticas de uma fase nemática calamítica - Lüders, Danilo Degan (2014)
In the present work, is investigated the reentrant isotropic (I RE) e calamitic nematic (NC) e isotropic (I) phase sequence in a ternary lyotropic mixture of potassium laurate (KL), decanol (DeOH), and deuterated water (D2O); and also the phase sequence NC e I for mixing of T TAB , HQO and DeOH. The calamitic nematic phases were firstly characterized by optical polarized light microscopy, digital image analysis and refractometry. Furthermore, it is investigated linear dichroism (absorption anisotropy) in the visible region and its dependence on the temperature. Through ordinary and extraordinary absorption coefficients at the wavelength of maximum absorption, the scalar order parameter is calculated along the range of NC phase. The entropy to referred to phase located between two isotropic phases is determined from Maier-Saupe's model and processing digital analysis technique. Concurrently with the linear optical response is also studied the nonlinear optical response by Z -scan technique, proposed by Sheik-Bahae in 1989, in the following phase I RE f Ng f I _ The normalized curve of transmittance in position function obtained by Z -scan is analyzed with base on the theoretical models proposed by Sheik- Bahae and Carter. Both models permit to determine the nonlinear refractive index ng, which is related to the real part of the third order tensor susceptibility X(3). In contrast, the thermotropic compound 5CB is also investigated in this work under the same experimental point of view, in reason of the existent analogy between the systems. The linear and nonlinear results from both compounds are analyzed and discussed, and compared with others results preexisting in the literature.